The effect of incubation temperature and site of sampling on assessment of the numbers of bacteria on red meat carcasses at commercial abattoirs. - Roberts, T. A. (Cambridge University Press, 1980)
Several sites on commercial beef, pork and lamb carcasses were sampled at the end of the slaughterline. Total viable counts (TVC) of bacteria were assessed by incubation at 37, 20 and 1 degree C in addition to presumptive coliforms (PC), Enterobacteriaceae (ENT) and faecal streptococci (FS). Statistical analyses showed consistently dirty sites within an abattoir but these sites varied from one abattoir to another. Inter-site differences were unaffected by the incubation temperature of the TVC. Numbers of PC, ENT and FS did not mimic TVC. Empirical sampling plans are proposed to detect the highest count on a carcass by bulking samples from known dirty sites. At the end of the slaughterline TVC 37 degrees C is the most useful bacteriological index.